2002
DOI: 10.1136/mp.55.6.374
|View full text |Cite
|
Sign up to set email alerts
|

Morphoea and Borrelia burgdorferi: results from the Scottish Highlands in the context of the world literature

Abstract: Aims: Previous studies investigating the link between infection with Borrelia burgdorferi and morphoea have produced conflicting results. Often, these studies have been undertaken in patients from different regions or countries, and using methods of varying sensitivity for detecting Borrelia burgdorferi infection. This study aimed to establish whether a relation could be demonstrated in the Highlands of Scotland, an area with endemic Lyme disease, with the use of a sensitive method for detecting the organism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 44 publications
0
13
0
4
Order By: Relevance
“…11 After the first report by Aberer, Neumann, and Stanek 6 in 1985 on an association between morphea and B burgdorferi infection, the pathogenic role of Borrelia in triggering morphea onset has been an open matter of intense debate. [12][13][14][15][16][17] Intrigued by 3 young patients suffering from severe or disseminated morphea in association with Borrelia infection, we reevaluated the enigmatic relationship between these two conditions and examined retrospectively a cohort of 90 morphea patients, identifying a unique autoimmune type of scleroderma in which B burgdorferi seems to have an important role.…”
Section: Introductionmentioning
confidence: 99%
“…11 After the first report by Aberer, Neumann, and Stanek 6 in 1985 on an association between morphea and B burgdorferi infection, the pathogenic role of Borrelia in triggering morphea onset has been an open matter of intense debate. [12][13][14][15][16][17] Intrigued by 3 young patients suffering from severe or disseminated morphea in association with Borrelia infection, we reevaluated the enigmatic relationship between these two conditions and examined retrospectively a cohort of 90 morphea patients, identifying a unique autoimmune type of scleroderma in which B burgdorferi seems to have an important role.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, subsequent reports with contradictory results were published. 4,5 Detection of Borrelia in morphea has been extensively reviewed by Weide et al 6 and Goodlad et al 7 These authors showed that an important challenge for the establishment of morphea and Borrelia association is the difficulty to detect the spirochete in tissue specimens. Most current borrelial detection methods lack sufficient sensitivity, so that even classical cutaneous borrelial infections rely on 1373 diagnosis based on circumstantial evidence combining clinicopathological, laboratorial information, and response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It can be triggered by physical trauma, infections or immunological changes. 55 In 1987 Aberer et al published the first study suggesting the association of scleroderma plaque and B. burgdorferi. 56 Subsequently, other authors also correlated sclerodermia and infection by B. burgdorferi.…”
Section: Other Skin Diseases Associated With Infection By Borreliamentioning
confidence: 99%